Structural Equation Modeling Applied to World-Class Maintenance Management in the Purification Subprocess of a Zinc Refinery - Blancas Hidalgo, José Luis (2025)
This article discusses the analysis of the current trend in world-class maintenance management, which involves identifying, quantifying, and managing assets in organizations and their productive processes, with the intention of contributing to development and sustainability. The importance of the study lies in the management of the purification subprocess of a zinc refinery in Peru, which is investigated from a world-class perspective and through factor analysis. The objective is to develop a factorial model of world-class maintenance management in the purification subprocess of a zinc refinery. The study population consisted of the work team from the maintenance, industrial safety, and operations areas of the purification subprocess at a zinc refinery in Peru. In the first phase, the consistency of the data obtained from a survey was determined, followed by descriptive correlational studies related to the pillars of world-class maintenance. In the second phase, the methodology of a structural equation model was applied to the data obtained in the first phase. As a result, it was determined that the factors of the structural model are information management and management framed in an innovative environment. The implementation of the world-class methodology concludes with a world-class availability of more than 90%.